Dossier 01 : Herinneringen en Feiten Lokaal 01 (1981-2006) - de Jong, Karin; Vergaert, Frederik; Peeters, Sef; Sprangers, Marianne; van Rosmalen, Ad; van Gerwen, Berry; Hui Lan, Linda Hoo; Iriks, Tom; Jongen, Sander; Monteiro, Bruno; Spruijt, Marijke; de Jong, Loes; et al. (Breda : Lokaal 01, 2007)
van de Camp, Geert ; Hocks, Teun ; Kemper, Margriet ; van der Stokker, Lily ; Peeters, Sef ; Horvers, Toine ; Lux, Harm ; van Hanegem, Ab ; de Vroom, Mélanie ; Van Den Dobbelsteen, Jan ; Nagtzaam, Marc ; van Rosmalen, Ad ; Lemaire, Danielle ; Kok, André ; et al.
Ter gelegenheid van het 25-jarig bestaan van Lokaal 01 in Breda/Antwerpen (11 december 2006 - 11 december 2007)
kunstcatalogus